Trauma patients with metastatic cancer undergoing emergent surgery: A matched cohort analysis - Matthew Nguyen; Jeffry Nahmias; Oliver S. Eng; Maheswari Senthil; Cristobal Barrios; Matthew Dolich; Michael Lekawa; Areg Grigorian (Surgery Open Science, 2024)
Background: There is a paucity of literature guiding trauma surgeons in the care of patients with active metastatic cancer (MC). Even less is known regarding outcomes for MC patients requiring emergent surgery after trauma. We hypothesized that trauma patients with active Metastatic Cancer (MC) have an increased mortality rate and undergo increased rates of withdrawal of care (WoC) within 72-hours following emergent operations, compared to similarly matched patients without MC. Methods: Patients with active MC at the time of traumatic injury were matched 1:2 against patients without active MC based on demographics, comorbidities, vital signs on admission, and injury profile. Results: From 43,826 patients, 0.2 % had MC. After matching 39 MC patients to 78 without MC, there was no difference in demographics, comorbidities, injury severity score, mechanism of injury, vitals on admission (blood pressure, heart rate, respiration rate) and need for blood transfusion (all p > 0.05). Compared to patients without MC, patients with MC had higher rates and associated risk of death during index hospitalization (38.5 % vs. 15.2 %, p = 0.005; OR 3.49, CI 1.43–8.51, p = 0.006), as well as a higher rate and associated risk of WoC within 72-hours (12.8 % vs. 1.3 %, p = 0.007; OR 11.47, CI 1.29–101.93, p = 0.029). Conclusion: Trauma patients with MC requiring emergent thoracic or abdominal surgery have a high risk of death and an over ten-fold higher associated risk for WoC within the first three days. In some cases, palliative care consultation should be considered, and counseling should be offered to this high-risk trauma population to enable individualized and patient-centric decisions. Key message: This research highlights the importance of a multidisciplinary team consisting of trauma surgeons, oncologist, and palliative care physicians in caring for the high-risk trauma patients with disseminated cancer requiring urgent surgery.